Andrea Long Chu and the Trouble with Desire - Koštal, Andrija (Identities: Journal for Politics, Gender and Culture, 2020)
This essay discusses the writings by Andrea Long Chu, focusing on her understanding of desire and its role in the formation of gender and in the process of gender transition. The essay also deals with her much-disputed understanding of the relation between desire and politics, taking into account the critique formulated by Amia Srinivasan. In conclusion the essay argues that Chu’s writings, if taken with a dose of caution and supplemented with the theory of desire formulated by Jacques Lacan, can offer us insights about the importance of desire for understanding various phenomena of human experience, in which we otherwise maybe wouldn’t look for it. Author(s): Andrija Koštal Title (English): Andrea Long Chu and the Trouble with Desire Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 70-74 Page Count: 5 Citation (English): Andrija Koštal, “Andrea Long Chu and the Trouble with Desire,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020): 70-74. Author Biography Andrija Koštal, Faculty of Humanities and Social Sciences in Zagreb Andrija Koštal is a student of comparative literature at the Faculty of Humanities and Social Sciences in Zagreb, about to graduate with a topic on the discourse of illness in a European modernist novel. His primary field of research concerns the relationship between literature and philosophy throughout the history of modernity (especially through the Twentieth century). On the part of philosophy, he is interested in the philosophy of immanence, non-philosophy/non-standard philosophy and some forms of materialism. Other areas of interest include artificial intelligence, ecology and feminism. Published a few articles in various Croatian scientific journals.